Under Discussion : The Encyclopedic Museum - Fumaroli, Marc; Grau, Donatien; Grau, Donatien (Book collections on Project MUSE., 2021)
"Are encyclopedic museums still relevant? In almost thirty interviews, Donatien Grau probes some of the world's most prominent thinkers, international arts officials, museum leaders, artists, architects, and arts journalists on the past, present, and future of the encyclopedic museum model"--